Hitting Walls (v. XXVIII): Captured Play. (November 2014) - Wing, Carlin
This article uses a thick description of a single point played by Ramy Ashour (Egypt) and James Wilstrop (England) during the finals of a professional squash tournament in 2008 to evoke the rhythms of virtuosic play and to describe the vast infrastructures we construct for its capture. I use the limits of the point to describe its preconditions—the body techniques, material technologies, and mediating architectures required for two professional players to have this single exchange. A sport's apparatus is the condition of possibility for its agile bodies. And while professional sport may seem quite distant from free or casual play, by understanding the labor that goes into producing spectacles of institutionalized play, we can gain better purchase on the multiple types of value that reside in, and are extracted from, our daily playing practices. When combined, economic and emotional stakes direct forms of play toward their physical, psychological, and spectacular limits.